2010
DOI: 10.1590/s1516-89132010000500030
|View full text |Cite
|
Sign up to set email alerts
|

Use of vinasse and sugarcane bagasse for the production of enzymes by lignocellulolytic fungi

Abstract: In this present work, three strains of Pleurotus and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 15 publications
0
16
1
4
Order By: Relevance
“…The chemical pretreatment for sugarcane bagasse developed by Aguiar et al (2010) to produce exoglucanases and endogluconases resulted in better breakage of the fibers when using 2% H 2 O 2 together with 1.5% NaOH at 121ºC for 15 min. This treatment increased the cellulose level up to 1.2 times and decreased the hemicellulose content 8.5 times, promoting a better accessibility of the fungi to the fibers.…”
Section: Alkaline Pretreatmentmentioning
confidence: 99%
“…The chemical pretreatment for sugarcane bagasse developed by Aguiar et al (2010) to produce exoglucanases and endogluconases resulted in better breakage of the fibers when using 2% H 2 O 2 together with 1.5% NaOH at 121ºC for 15 min. This treatment increased the cellulose level up to 1.2 times and decreased the hemicellulose content 8.5 times, promoting a better accessibility of the fungi to the fibers.…”
Section: Alkaline Pretreatmentmentioning
confidence: 99%
“…47 High alkali concentration increases treatment costs, and leads to more sewage production. 19,20 Therefore, 1.5% NaOH was selected for the following experiments. It is worth noting that the straw particle size in this study was much bigger and the processing temperature much lower than those of other studies.…”
Section: Pretreatment Of Corn Stalkmentioning
confidence: 99%
“…The combination of alkali pretreatment with other physical or chemical methods usually improves delignification efficiency and reduces process severity. 19,20,21 As a result, toxic compounds and pollutant production are reduced. It has been shown that ultra-high pressure explosion combined with treatment with 0.5% NaOH at 125…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species has a worldwide distribution and can be found in tropical or subtropical forests (Guerrero and Homrich, 1999;Putzke, 2002;Rosado et al, 2002). This mushroom has been produced in vitro in several agro-industrial substrates as castor plant peel, rice straw, sugarcane bagasse, cotton waste, soybean straw, corn cob, elephant grass, oat, rye grass, sunflower seed, eucalyptus sawdust, stillage and privet (Rosado et al, 2002;Donini et al, 2005;Bernardi et al, 2007;Minotto et al, 2008;Nascimento et al, 2008;Aguiar et al, 2010;Reis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%